2017
DOI: 10.1021/acs.jpcc.6b10268
|View full text |Cite
|
Sign up to set email alerts
|

Li/Li7La3Zr2O12/LiFePO4 All-Solid-State Battery with Ultrathin Nanoscale Solid Electrolyte

Abstract: We introduced the nanoconcept in the oxide solid electrolyte Li7La3Zr2O12 (LLZO). All-solid-state Li/LiFePO4 (LFPO) cell using this solid electrolyte with thickness of several micrometers was assembled with appropriate solvent, dispersant, adhesives, and surfactant without cold- or hot-pressing. At room temperature, the Li/LLZO/LFPO cell showed the first discharge capacity of 160.4 mAh g–1, which was 94.4% of the theoretical capacity of LFPO, and the cell provided a discharge capacity of 136.8 mAh g–1 after 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…As a result, the number of Li ions (or atoms) is beyond the number of tetrahedral sites, resulting in the occupation of octahedral sites by excess Li and shortening of the Li-Li distance. The electrostatic repulsion between the fairly close Li ions, together with the dynamic process, pushes Li ions to move along the transport channels in the LLZTO crystal (49). Previous ab initio calculations revealed that Li ions migrated in a priority sequence of octahedral site, tetrahedral site, and vacant octahedral site (27).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the number of Li ions (or atoms) is beyond the number of tetrahedral sites, resulting in the occupation of octahedral sites by excess Li and shortening of the Li-Li distance. The electrostatic repulsion between the fairly close Li ions, together with the dynamic process, pushes Li ions to move along the transport channels in the LLZTO crystal (49). Previous ab initio calculations revealed that Li ions migrated in a priority sequence of octahedral site, tetrahedral site, and vacant octahedral site (27).…”
Section: Resultsmentioning
confidence: 99%
“…We further evaluated the activity and extensive applicability of LLZTO@LCO by adding it to LiFePO 4 cathodes with a low ionic diffusion rate. The prepared LLZTO@LCO-containing LiFePO 4 (LFP-LLZTO@LCO) composite cathode and LLZTO@Li 2 CO 3 -containing LiFePO 4 (LFP-LLZTO@Li 2 CO 3 ) composite cathode (Fig. 7a) were assembled into SSBs using a lithium anode and a LLZTO solid electrolyte pellet, separately.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the SSEs are completely non-wetting compared with the liquid electrolyte so that the electrolyte cannot be immersed in the cathode to construct lithium-ion transport pathways, slowing the diffusion of lithium ions between particles inside the cathode. In order to address this issue, solid electrolyte powders are often added to the cathodes and the interface between solid electrolytes and active materials is designed to increase the ionic conductivity and decrease the polarization of electrode [2][3][4][5] . In the recent year, the SSBs employing a garnetstructured Li 7 La 3 Zr 2 O 12 (LLZO) electrolyte have shown significant promise in practical applications because the LLZO electrolyte has high lithium-ion conductivity and is stable to lithium metal, but again, the ionic conductivity inside the cathode is low due to the use of the non-wetting LLZO solid electrolyte piece.…”
mentioning
confidence: 99%
“…The undersigned agree to abide by the statements . [12][13][14][15] The composite microstructure is expected to provide sufficient electron and ion transport, however, the design principles of these electronic-ionic composites are largely unknown and need to be determined.…”
Section: Review Approval and Acceptance Review Approval And Acceptancementioning
confidence: 99%